RANCANG BANGUN PENGOLAHAN CITRA DIGITAL PADA SISTEM PENDETEKSI LANDASAN PACU - , AHMAD MUZAKKY; , R. Sumiharto, S.Si, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A design of digital image processing on runway detection system had been created. These runway detection system was created by utilizing computer vision.Methods used in this system are region of interest, grayscale, canny edge detection and hough transform. In order to provide sufficient data in image processing, a video of the runway was taken before. Thus, the image being processed through several methods. Those methods are image preprocessing, followed by grayscale, canny edge detection and hough transform to detect lines runway. The coordinate points of detected line then sent to the microcontroller to be processed and generates ruder servo movement on the aircraft. Programming used in the manufacture of this runway detection system is OpenCV 2.4.3 and Visual Studio 2010. The programming language used is C + + language The test performed using a runway video that has been taken directly at the runway behind STTA Adisucipto aeromodelling ground, Yogyakarta. The test gave satisfactory result, the system capable of detecting the best runway when hough tranform given filter angle of 5-7 degrees. The system is capable of detecting ground well at a height of up to 8 meters above the ground. And its able to detect runway well when the video taken with plane speeds up to 60 km / hour.